Diphyllobothriidae cestode parasites of flounders Paralichthys patagonicus (Jordan, 1889) and Xystreurys rasilis (Jordan, 1891) collected off the coast of Rio de Janeiro, Brazil - FONSECA, Michelle Cristie Gonçalves da; FELIZARDO, Nilza Nunes; GOMES, Delir Corrêa; São CLEMENTE, Sergio Carmona de; KNOFF, Marcelo (Food Science and Technology, 2025)
The present paper is a continuation of the survey about helminths parasitizing the flounders, Paralichthys patagonicus and Xystreurys rasilis, marine fish purchased from fish markets in the municipalities of Cabo Frio, Niterói, Rio de Janeiro, and Angra dos Reis, Rio de Janeiro State, Brazil. Specifically, this paper reports the results of an investigation concerning Diphyllobothriidae cestodes parasitizing these hosts. A total of 72 fish specimens were caught by professional fishermen off the coast of Rio de Janeiro State. The fish were measured and necropsied, and their organs were investigated for Diphyllobothriidae cestodes. A total of 12 flounders were parasitized by 23 specimens of Diphyllobothriidae gen. sp., infecting the stomach, intestinal serosa, abdominal cavity, and abdominal musculature. The taxonomic identification of these parasites was based on morphological and morphometric characteristics using bright-field microscopy. The specimens were identified as Diphyllobothriidae gen. sp., and their parasitic indices were presented. This is the first record of Diphyllobothriidae gen. sp. parasitizing the flounders P. patagonicus and X. rasilis in South America. The presence of these cestode plerocercoids is worrisome because of the potential risk of diphyllobothriasis, thereby reinforcing the hygienic-sanitary significance of monitoring these parasites.